A New Properties of Bajakah Tampala Wood (Spatholobus littoralis Hassk) Ethanol Extract Against -Amylase Inhibition as Candidate Antidiabetic and Its Fortification in Kapok Honey - Anggriani, Rista; Harini, Noor; Husna, Afifa; Sukardi, Sukardi; NS, Maureen Danysha (Agriculture Faculty, 2024)
Bajakah Tampala extracted with ethanol was indicated to contain phenolic and flavonoids. So far, the ethanol extract of Bajakah Tampala wood has only been analyzed for its antioxidant activity. Whereas flavonoids not only act as antioxidants but also play a role in inhibiting -amylase which is related to antidiabetic properties. The ethanol extract of Bajakah Tampala wood has never been used as a fortificant in honey. The purpose of this study was to determine the levels of phenols, flavonoids, antioxidant activity, and inhibitory activity of -amylase from the ethanol extract of Bajakah Tampala Wood (EEBTW) at various solvent concentrations. In addition, to investigate the effect of adding EEBTW to Kapok honey on its bioactivity. This study was conducted using Post Test Only Group Design that was applied to 1% fortification of the three extracts in Kapok honey. Extraction used three concentrations of ethanol (70%, 80%, and 90%). Parameters tested in the study were total phenol, total flavonoid, antioxidant activity, and % inhibition of -amylase. The result showed the higher the ethanol concentration, the lower the total phenolic, flavonoid, % DPPH scavenging activity, and -amylase inhibition. The addition of 1% EEBKT has synergism with brown honey in increasing phenol, antioxidant activity, and % inhibition of -amylase. EEBTW has the potential as an antidiabetic candidate and Kapok honey with EEBTW has the potential as functional honey